2014
DOI: 10.1093/cvr/cvu182
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac hypertrophy in mice expressing unphosphorylatable phospholemman

Abstract: AimsElevation of intracellular Na in the failing myocardium contributes to contractile dysfunction, the negative force–frequency relationship, and arrhythmias. Although phospholemman (PLM) is recognized to form the link between signalling pathways and Na/K pump activity, the possibility that defects in its regulation contribute to elevation of intracellular Na has not been investigated. Our aim was to test the hypothesis that the prevention of PLM phosphorylation in a PLM3SA knock-in mouse (in which PLM has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 34 publications
(41 reference statements)
4
56
0
Order By: Relevance
“…Recently, Boguslavskyi et al . () and Correll et al . () have reported a reduction in both PLM expression and phosphorylation in mouse models of hypertrophy that, in the Boguslavskyi study, has been directly related to declining Na + /K + pump function and intracellular Na + elevation.…”
Section: The Na+/ca2+ Exchanger – Structure Function and Regulationmentioning
confidence: 86%
See 3 more Smart Citations
“…Recently, Boguslavskyi et al . () and Correll et al . () have reported a reduction in both PLM expression and phosphorylation in mouse models of hypertrophy that, in the Boguslavskyi study, has been directly related to declining Na + /K + pump function and intracellular Na + elevation.…”
Section: The Na+/ca2+ Exchanger – Structure Function and Regulationmentioning
confidence: 86%
“…, b ; Boguslavskyi et al . ). Specifically in cardiac hypertrophy many studies have shown that Na + /K + pump function, and/or expression, is reduced (Pogwizd et al .…”
Section: The Na+/ca2+ Exchanger – Structure Function and Regulationmentioning
confidence: 97%
See 2 more Smart Citations
“…DHHC5 therefore inhibits the pump through both palmitoylation of PLM and the MEND pathway. The convergence of multiple signaling pathways on PLM highlights the key role of this regulatory protein in control of intracellular Na in cardiac myocytes (30). Intracellular Na influences a vast array of cellular processes in the heart (12), including contractility via NCX and mitochondrial energetics (31).…”
Section: Discussionmentioning
confidence: 99%